Empowering youth as agents of change: Gaps and opportunities for meaningful youth engagement (MAYE) for sustainable nutrition, climate and public health programmes - Joseph Gaithuma; Samuel Chor; Angela Natukunda; Pturgo Shahleen; Justine A. Kavle (Maternal and Child Nutrition)
Abstract Addressing the intersection of food insecurity, malnutrition and climate change in Sub‐Saharan Africa requires meaningful adolescent and youth engagement to drive sustainable change. Drawing on empirical evidence and collective experiences from youth‐led initiatives and coalitions, four gaps and opportunities to better involve youth in programmes are discussed, including, the need to: (1) standardise the definition of youth to improve programme design and data harmonisation, (2) provide capacity building and mentorship for youth leadership in health service delivery, (3) foster youth leadership and multisectoral collaboration in food and health systems and (4) enhance capacity development for non‐youth actors to support genuine youth participation. This viewpoint underscores the importance of involving African youth in public health nutrition, climate change and food security programmes design and implementation—as drivers of change to addressing hunger and climate crises. By centering youth voices and experiences, programmes and policies can better address African communities' complex challenges, fostering inclusivity, sustainability and resilience in achieving better nutrition and public health programmes and outcomes.